Community-based Ecotourism Strategy for Local Economic Empowerment - Irmawati Irmawati; Hasnawati Hasnawati (Mahesa Research Center, 2024)
This study aims to analyze community-based ecotourism strategies to empower the local economy in Bone Regency. Using qualitative methods and a case study approach, this research involved 20 informants consisting of 10 domestic tourists, 5 tourism agency employees, and 5 members of the environmental community. Data were collected through in-depth interviews, field observations, and documentation, then analyzed thematically. The results showed that the implementation of community-based ecotourism strategies was able to have a positive impact on the local economy. Communities are actively involved in the management of ecotourism destinations, which not only increases their income but also strengthens awareness of the importance of preserving the environment. Community participation in environmental conservation and tourism management, such as waste management and ecosystem conservation, has proven to be an important factor in the success of ecotourism. In addition, the role of local government and the environmental community plays a significant role in supporting the sustainability and development of ecotourism. This study concludes that community-based ecotourism strategies can be an effective model of local economic empowerment, but further collaboration between the government, communities, and tourists is needed to improve social and environmental impacts sustainably.